Quality of Antimalarial Drugs Analysed in the National Quality Control Laboratory during the Period 2002–2005 (The East and Central African Journal of Pharmaceutical Sciences, 2018)
During the period 2002–2005, the National Quality Control Laboratory analysed 229 samples of antimalarial drugs. In 2002, 42% of these products failed to comply with compendial specifications, with the sulfadoxine/ sulfamethoxypyrazine and pyrimethamine combination products forming 39% of the total failures. The respective percentages were 46% and 84% for 2003 and 36% and 72% for 2004. By May 2005, the only failures reported were of sulfadoxine/sulfamethoxypyrazine and pyrimethamine combination products. Until recently, sulfadoxine/sulfamethoxypyrazine and pyrimethamine combination products were the first-line malaria treatment regimen in Kenya. These analytical results raise concerns that the reported therapeutic failures associated with the use of these products could possibly be due to the administration of sub-standard sulfadoxine/sulfamethoxypyrazine and pyrimethamine combination products to patients. The same could be true of artemisinin based combinations which are the current first-line treatment regimen if the observed trend continues
Keywords: Antimalarials; dissolution; assay; quality control tests